Capturing northern biodiversity: diversity of arctic, subarctic and north boreal beetles and spiders are affected by trap type and habitat. Issue 1 (9th October 2015) - Ernst, Crystal M.; Loboda, Sarah; Buddle, Christopher M.
Abstract: Rapid environmental changes in arctic, subarctic and boreal biomes are fuelling the need for effective biodiversity monitoring programs in these regions. Terrestrial arthropods are ideal focal taxa for monitoring, but quantitative comparisons of the efficacy and outcomes of different sampling protocols are limited. Here, the influence of trap type (yellow pan trap or traditional pitfall) and habitat (wet or mesic) on the abundance and diversity of ground‐dwelling arthropods is determined for samples collected in the three northernmost ecoclimatic zones of Canada, using over 32 000 specimens of beetles and spiders. Trap and habitat both influence the abundance, richness, and assemblage composition of arthropods collected, but these effects differ between ecoclimatic zones and depend on taxonomic resolution. Sampling in different habitats yields greater diversity than sampling with different traps in the high arctic, while the inverse is true in the north boreal zone, and neither factor appears to have a significant effect on the diversity of arthropods collected in the subarctic. In all zones, the addition of recessed yellow pan traps to a traditional pitfall trap‐based sampling regime results in the capture of many additional unique species, suggesting that colour is an attractant for at least some ground‐dwelling taxa. These findings have significant implications for large‐scale terrestrial diversity monitoring programs being established or implemented in northern systems. It is recommended that sampling regimes be designed to maximize the diversity of arthropods collected, by including a minimum of two distinct habitats and by using yellow pitfall traps.